THE SURVIVAL PREDICTORS OF CARDIAC DEATH, LETHALITY PREDICTION IN THE DOGS WITH COMBINED MITRAL-TRICUSPID INSUFFICIENCY - Руденко, А. А. (Scientific Progress & Innovations, 2013)
Basing on results of the plural Cox’s analysis of proportional intensities three independent predictors of a lethal outcome of illness are detected. They are: presence of pulmonary edema, sex, functional class of chronic cardiovascular failure. The effective model of a lethality prediction in sick dogs during one year of supervising, taking into account the main independent predictors, is developed. The received model is characterized by high level of self-descriptiveness (83,1 %), sensitivity (85,7 %) and specificity (77,8 %).